EXPLORING THE RELATIONSHIP BETWEEN SMART CITY, SUSTAINABLE DEVELOPMENT AND INNOVATION AS A MODEL FOR URBAN ECONOMIC GROWTH - Procopie Florin Gușul (University of Oradea, 2021)
In this paper we focus on the concept of smart city, defined as cities where investments in human and social capital and infrastructure, along with ICT progress and innovation fuel the sustainable economy and stimulate growth in quality of life, with a focus on smart natural resource management. We envision smart city as a concept that highlights important aspects of sustainability, such as the need for responsible resource management, energy efficiency and citizen involvement. Given the current understanding of the smart city concept, it is unclear whether it has the necessary features to ensure sustainability. We believe that this aspect is due to the fact that smart cities are extremely complex and interdependent. Their study and analysis would therefore require an inter- and transdisciplinary approach that allows an adequate overview of this concept, to the convergence of several areas, such as urban development, technology, economics, engineering and social sciences, etc. We believe that this research will contribute to the already existing theories of smart cities and will help maximize the potential for this smart city concept to be a viable solution for sustainable development in our increasingly urbanized world, especially as the latest statistics confirm an upward trend in EU-level indicators on sustainable cities and communities. Moreover, the theory of smart growth is being discussed, but not as an antagonist alternative, but rather as an addition integrative to the concept of sustainable development of smart cities. In our opinion, smart city solutions would not be efficiently implemented and helpful to communities in absence of a vision for the smart and sustainable future.